2021
DOI: 10.1002/stem.3453
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclin-Like Protein SPY1 Overrides Reprogramming Induced Senescence Through EZH2 Mediated H3K27me3

Abstract: Fully differentiated cells can be reprogrammed through ectopic expression of key transcription factors to create induced pluripotent stem cells. These cells share many characteristics of normal embryonic stem cells and have great promise in disease modeling and regenerative medicine. The process of remodeling has its limitations, including a very low efficiency due to the upregulation of many antiproliferative genes, including cyclin dependent kinase inhibitors CDKN1A and CDKN2A, which serve to protect the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…As a result of this mechanism Spy1 has been isolated from numerous screens and has been described for the ability to override cell cycle arrest mechanisms including DNA damage and cellular senescence 19,20 . Data from our lab show that Spy1 can enhance pluripotent reprograming by epigenetic downregulation of CDK inhibitors and is essential for overcoming reprogramming-induced senescence 21 . Work from the Nebreda lab has recently demonstrated that Spy1 is required for activation of NSCs out of quiescent state via activation of CDK2 22 .…”
Section: Introductionmentioning
confidence: 98%
“…As a result of this mechanism Spy1 has been isolated from numerous screens and has been described for the ability to override cell cycle arrest mechanisms including DNA damage and cellular senescence 19,20 . Data from our lab show that Spy1 can enhance pluripotent reprograming by epigenetic downregulation of CDK inhibitors and is essential for overcoming reprogramming-induced senescence 21 . Work from the Nebreda lab has recently demonstrated that Spy1 is required for activation of NSCs out of quiescent state via activation of CDK2 22 .…”
Section: Introductionmentioning
confidence: 98%
“…Several publications have implicated Spy1 in expanding normal and cancer stem cell populations in the brain [28, 32, 33]. Recently, Spy1 has been shown to activate the epigenetic regulator EZH2 and support reprogramming to a pluripotent state [34]. Whether Spy1-mediated effects on stemness have any implications in the mammary gland was not previously addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have implicated Spy1 in expanding normal and cancer stem cell populations in the brain [ 28 , 32 , 33 ]. Recently, Spy1 has been shown to activate the epigenetic regulator EZH2 and support reprogramming to a pluripotent state [ 34 ]. Whether Spy1-mediated effects on stemness have any implications in the mammary gland was not previously addressed.…”
Section: Introductionmentioning
confidence: 99%